Numerical solution of non-Newtonian fluids flow past an accelerated vertical infinite plate in the presence of free convection currents - Patel, Manisha; Timol, Munir Gulam (Zielona Góra: Uniwersytet Zielonogórski)
A similarity analysis of non-Newtonian fluid flow past an accelerated vertical infinite plate in the presence of free convection current is carried out. A group theoretic generalized dimensional analysis is employed to achieve the governing non-linear ordinary differential equations in the most general form. Numerical solutions of these equations are given with the plot of their velocity profiles with the effects of Pr-Prandtl number and Gr-Grashof number.
Keywords: non-Newtonian fluid; convection currents; similarity analysis